HUBUNGAN BUDAYA ORGANISASI DENGAN PENERAPAN (GHG) GOOD HOSPITAL GOVERNANCE RUMAH SAKIT TK. II BHAYANGKARA MAKASSAR - Reza Nur; Dian Ekawaty; Sriyani Windarti; Nurmulia Wunaini Ngkolu (Institut Kesehatan Pelamonia, 2024)
Hospital Governance is a legal product which is a hospital bylaw set by the hospital owner, which contains hospital organization regulations (corporate bylaws) and hospital medical staff regulations (medical staff bylaws) which are prepared in the context of implementing governance. This study aims to determine the relationship between organizational culture and (GHG) good Hospital Governance Bhayangkara Hospital TK.II Makassar. The type of research used is descriptive quantitative research with a cross sectional study approach. The sample in this study was 136 respondents. The data of this research were taken through questionnaires and direct observation and the data analysis technique used multiple linear regression test with the help of SPSS. The results of this study indicate an assessment of the variable values ​​obtained by sig = 0.031 <0.05. Confidence variable obtained sig value 0.045 <0.05. Organizational Climate variable obtained sig value = 0.026 <0.05. Tradition variable is obtained sig = 0.020 <0.05. The conclusion in this study is that the variables of belief, organizational climate and tradition have a significant relationship to Good Hospital Governance Bhayangkara Hospital TK. II Makassar